The Influence of Work Environment and Work Discipline on the Performance of the Regional Police Force in Samarinda City - Kharisma, Yuphie; Kharista, Malinda; Hakim, Yundi Permadi; Sadarrudin, Muh. Alvianto Putra Arizandi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to analyze the influence of the work environment and work discipline on the performance of the Civil Service Police Unit (Satpol PP) in Samarinda City. Data was collected through questionnaires distributed to Satpol PP members and analyzed using the multiple regression method. The results of the analysis show that together, the work environment and work discipline have a significant influence on the performance of Satpol PP. However, when viewed partially, the work environment only has a positive but not significant influence on performance, while work discipline has a positive and significant influence on performance. These findings show the importance of work environment factors and work discipline in improving the performance of Satpol PP. The practical implication of this research is the importance of paying attention to aspects of the work environment and work discipline in the management of the Satpol PP organization to increase effectiveness and efficiency in carrying out their duties as law enforcers in Samarinda City.